Driving Energy Consumption of Electric Traction Vehicles - Bojan Cene; Aleksandar Radosavljevic; Branislav Gavrilovic (Communications - Scientific letters of the University of Zilina, 2008)
The paper presents some simulation and tests results of driving energy consumption of electric traction vehicles both at Serbian and Slovenian Railways. On Serbian Railways there are two series of electric locomotives: four-axles 441 series made in former Yugoslavia under license of ASEA (Sweden) and six-axles 461 series manufactured in Romania in co-operation with ASEA. On Slovenian railways are four series of electrical locomotives operating: the Italian two axles locomotive series 342, the Italian six axles locomotive series 362, the French six axles locomotive series 363, and the three-system four axles Siemens locomotive series 541.